Search for familial clustering of multiple myeloma with any cancer - Frank, Christoph; Fallah, M.; Chen, T.; Mai, Elias K.; Sundquist, J.; Försti, A.; Hemminki, K. (Leukemia, 2016)
Multiple myeloma (MM) is a disease of immunoglobulin-producing plasma cells, which reside mainly in the bone marrow. Family members of MM patients are at a risk of MM, but whether other malignancies are in excess in family members is not established and is the aim of this study. MM patients (24 137) were identified from the Swedish Cancer Registry from years 1958 to 2012. Relative risks (RRs) were calculated for MM defined by any cancer diagnosed in first-degree relatives and compared with individuals whose relatives had no cancer. MM was reliably associated with relative’s colorectal, breast and prostate cancers, non-thyroid endocrine tumors, leukemia and cancer of unknown primary; in addition, MM was associated with subsites of bone and connective tissue tumors and of non-Hodgkin lymphoma, including lymphoplasmacytic lymphoma/Waldenström macroglobulinema (RR 3.47). MM showed a strong association (RR 1.91) in colorectal cancer families, possibly as part of an unidentified syndrome. All the associations of MM with discordant cancers are novel suggesting that MM shares genetic susceptibility with many cancers. The associations of MM bone and connective tissue tumors were supported by at least two independent results. Whether the results signal bone-related biology shared by MM and these tumors deserves further study.
advance online publication, 17 November 2015
Gesehen am 11.03.2020